2022
DOI: 10.3390/su142114350
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Scientific and Technical Activities on the Economic Growth of World Countries

Abstract: At present, scientific and technical activities (STA) play a fundamental role in the creation of new knowledge necessary for the realisation of the goals of sustainable economic growth. The purpose of the research is to assess STA in countries of the world and Ukraine as well as to analyse the impact of STA on their sustainable economic growth. For the assessment of STA of world countries, we have developed a composite indicator (Index of STA–ISTA) based on two sub-indices (Potential of STA and Results of STA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…The results are contrary to the results obtained in this analysis, as the results showed a strong correlation of all the studied variables. Research results brought by Ma et al [25] made it possible to demonstrate the existence of a moderately positive impact of environmental technologies and innovations on accelerating innovative development, improving the quality of life of the population and GDP per capita growth. The study by Hung [26] also investigated the relationship between GDP and HDI in China during the 1990-2019 period.…”
Section: Discussionmentioning
confidence: 99%
“…The results are contrary to the results obtained in this analysis, as the results showed a strong correlation of all the studied variables. Research results brought by Ma et al [25] made it possible to demonstrate the existence of a moderately positive impact of environmental technologies and innovations on accelerating innovative development, improving the quality of life of the population and GDP per capita growth. The study by Hung [26] also investigated the relationship between GDP and HDI in China during the 1990-2019 period.…”
Section: Discussionmentioning
confidence: 99%
“…Moving forward, the literature discussed the inadequate use of one single dimension, such as 'income', in clustering units with regard to innovation, besides, the fact that 'income' is not one of the innovation indicators (Ma et al, 2022;Stefko et al, 2019;Liudmyla et al, 2022;Jankowska et al, 2017). To name but a few, Ma et al (2022) calculated an index for the scientific and technical activities that are necessary for knowledge creation and sustainable growth. They utilized all the indicators to group all countries into three clusters: leaders, potential leaders and catching-up countries.…”
Section: Innovation Performance Benchmarkingmentioning
confidence: 99%
“…According to Guner [35], France, although it scored among the top 12 countries globally in the GII, still needs to strengthen its science and research infrastructure to match its economic size and potential [36]. Indeed, as France has paid attention to Science and Technical Activities (STA) development that resulted in scientific and technical that contributed to innovation development, France is considered among potential countries to become STA World Leaders [37].…”
Section: Francementioning
confidence: 99%
“…As a major hub for research and development as well as innovation, Japan scored in the top five G8 countries in the GII 2022 Rankings and 13th globally. Indeed, recent research indicated that Japan has been classified as among the group of countries that are leaders in STA (high potential and results), which is an indication that Japan has been developing processes and policies that enable new knowledge generation and implementation [37]. Additionally, the economic growth of Japan is influenced by the Nation's proportion of R&D expenditure from its GDP as well as the number of qualified workforce, were all scored high levels compared to G8 countries [38].…”
Section: Japanmentioning
confidence: 99%